2011
DOI: 10.1007/s11664-011-1747-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bonding Parameters on the Interaction Between Cu and Noneutectic Sn-In Solder Thin Films

Abstract: Thermocompression bonding of through-layer copper interconnects is of great interest for fabrication of three-dimensional (3D) integrated circuits. We have investigated interactions of Cu films with noneutectic Sn-In at length scales of 1 lm to 5 lm. The effects of bonding time, bonding temperature, and postbonding annealing temperature on intermetallic compound (IMC) formation, joint microstructure, and shear strength were investigated using scanning electron microscopy (SEM), energy-dispersive x-ray spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Out of the many solder combinations, Sn-In is a promising candidate for lowering the bonding temperature due to its low melting point [7]. In a previous work, we have demonstrated that Sn 75 In 25 can bond to Cu at 200 °C with an acceptable shear strength [3,6]. This was a substantial temperature reduction compared to typical pure Sn solders, which bond at around 280 °C [8,9].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Out of the many solder combinations, Sn-In is a promising candidate for lowering the bonding temperature due to its low melting point [7]. In a previous work, we have demonstrated that Sn 75 In 25 can bond to Cu at 200 °C with an acceptable shear strength [3,6]. This was a substantial temperature reduction compared to typical pure Sn solders, which bond at around 280 °C [8,9].…”
Section: Introductionmentioning
confidence: 85%
“…where k 1 , k 2 and k 3 are the spring constants of the cantilever at locations 1, 2 and 3, which are separated by a known separation distance (d). The cross sectional stiffness (S) can then be determined by taking the slope of k 1/3 versus L. Subsequently, Young's modulus (E) can be computed using equation (3).…”
Section: Young's Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…With low temperature processing, this can lead to the precipitation of a Sn-In IMC that melts at 222°C, and therefore, does not offer any advantages over conventional Pb-free solder alloys. In contrast, the ternary Cu-Sn-In is a promising LPDB system because the Cu6(Sn, In)5 phase in equilibrium with neareutectic liquid compositions incorporates both components of the LTP, as seen in the calculated Cn-Sn-In isothermal section of the ternary phase diagram in Fig.10, and has been shown to solidify isothermally by Sasangka et al [81] . The ternary Ni-Sn-In exhibits similar characteristics to Cu-Sn-In, but the solubility of In in Ni3Sn4 is more limited.…”
Section: In-sn Ltp With Ag Cu or Nimentioning
confidence: 99%
“…With low temperature processing, this can lead to the precipitation of a Sn-In IMC that melts at 222°C, and therefore, does not offer any advantages over conventional Pb-free solder alloys. In contrast, the ternary Cu-Sn-In is a promising LPDB system because the Cu 6 (Sn, In) 5 phase in equilibrium with near-eutectic liquid compositions incorporates both components of the LTP, as seen in the calculated Cn-Sn-In isothermal section of the ternary phase diagram in Fig.10, and has been shown to solidify isothermally by Sasangka et al [81] The ternary Ni-Sn-In exhibits similar characteristics to Cu-Sn-In, but the solubility of In in Ni 3 Sn 4 is more limited. As with the Ag-In-Sn system, alloys of In-rich Ni-Sn-In are likely to form undesirable low-melting temperature In-Sn IMCs rather than Ni 3 (Sn, In) 4 .…”
Section: Potential Lpdb Systemsmentioning
confidence: 99%